Trust and Security in Collaborative Computing. - Zou, Xukai (Computer and network security., 2008)
Computer networks are compromised by various unpredictable factors, such as hackers, viruses, spam, faults, and system failures, hindering the full utilization of computer systems for collaborative computing - one of the objectives for the next generation of the Internet. It includes the functions of data communication, resource sharing, group cooperation, and task allocation. One popular example of collaborative computing is grid computing. This monograph considers the latest efforts to develop a trusted environment with the high security and reliability needed for collaborative computing. Th.